Self- directed learning : critical practice - Hammond, Merryl; Collins, Rob. (London : NICHOLS/GP Publishing, 1997)
Aimed at those educators who wish to make their practice more consistent with progressive educational principles, namely helping learners to take greater control over planning and managing their own learning. The book contains a balance of theory and practical suggestions.
Includes References and index.
Keywords: Adult education; Continuing education; Critical thinking; Individualized instruction; Learning -- Evaluation; Adult learning